2011
DOI: 10.1124/jpet.111.180208
|View full text |Cite
|
Sign up to set email alerts
|

Previous Exposure to Δ9-Tetrahydrocannibinol Enhances Locomotor Responding to but Not Self-Administration of Amphetamine

Abstract: Previous exposure to amphetamine leads to enhanced locomotor and nucleus accumbens (NAcc) dopamine (DA) responding to the drug as well as enhanced amphetamine self-administration. Here, we investigated the effects of exposure to ⌬ 9 -tetrahydrocannibinol (⌬ 9 -THC) on behavioral and biochemical responding to amphetamine. Rats in different groups received five exposure injections of vehicle or one of five doses of ⌬ 9 -THC (0.4, 0.75, 1.5, 3.0, and 6.0 mg/kg i.p.) and were tested 2 days and 2 weeks later. Expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…They are also consistent with other reports supporting a relation between sensitized midbrain dopamine neuron reactivity and enhanced stimulant self-administration [5, 9, 16, 17, 33]. Together with these findings, the present results support an incentive motivational view of enhanced nicotine intake [8, 9, 34, 35] and the suggestion by some that it is the changes in mesoaccumbens dopamine function induced by previous exposure to nicotine [1] that predisposes individuals to pursue this drug [2, 3].…”
Section: Discussionsupporting
confidence: 93%
“…They are also consistent with other reports supporting a relation between sensitized midbrain dopamine neuron reactivity and enhanced stimulant self-administration [5, 9, 16, 17, 33]. Together with these findings, the present results support an incentive motivational view of enhanced nicotine intake [8, 9, 34, 35] and the suggestion by some that it is the changes in mesoaccumbens dopamine function induced by previous exposure to nicotine [1] that predisposes individuals to pursue this drug [2, 3].…”
Section: Discussionsupporting
confidence: 93%
“…There is further evidence of downstream dopaminergic effects of THC, as one study in rats78 reported up-regulated postsynaptic dopamine receptor signalling in the NAc via increased adenylyl cyclase activity, which was proposed to underlie THC-induced changes in amphetamine-induced locomotive behaviour. These findings suggest that repeated THC dosing results in altered dopamine receptor signal transduction.…”
Section: Repeated Thc and Post-synaptic Dopaminementioning
confidence: 99%
“…Indeed, while pre-exposure to THC does not appear to affect the self-administration of AMPH in rats [178], the blockade of CB 1 receptors attenuates METH self-administration [179,180]. Notably, this effect may not reflect an intrinsic reduction of the rewarding properties of METH, but rather the acquisition and consolidation of the preference for this drug [181,182], suggesting that the key effect of cannabis may modulate the plastic and adaptive response to repeated administrations of ATSs.…”
Section: Effects Of Meth and Cannabis On Abuse And Dependencementioning
confidence: 95%